Soft-assembled Multilevel Dynamics of Tactical Behaviors in Soccer - Ric, Angel; Torrents, Carlota; Gonçalves, Bruno; Sampaio, Jaime; Hristovski, Robert (Frontiers in Psychology, 2016)
This study aimed to identify the tactical patterns and the timescales of variables during a soccer match, allowing understanding the multilevel organization of tactical behaviors, and to determine the similarity of patterns performed by different groups of teammates during the first and second halves. Positional data from twenty professional male soccer players from the same team were collected using high frequency global positioning systems (5Hz). Twenty-nine categories of tactical behaviors were determined from eight positioning-derived variables creating multivariate binary (Boolean) time-series matrices. Hierarchical principal component analysis was used to identify the multilevel structure of tactical behaviors. The sequential reduction of each set level of principal components revealed a sole principal component as the slowest collective variable, forming the global basin of attraction of tactical patterns during each half of the match. In addition, the mean dwell time of each positioning-derived variable helped to understand the multilevel organization of collective tactical behavior during a soccer match. This approach warrants further investigations to analyze the influence of task constraints on the emergence of tactical behavior. Furthermore, principal component analysis can help coaches to design representative training tasks according to those tactical patterns captured during match competitions and to compare them depending on situational variables.